ОҚЫТЫЎШЫЛАРДА ПЕДАГОГИКАЛЫҚ ШЕБЕРЛИКТИҢ ҚӘЛИПЛЕСИЎИ - Қурбанбаева, Б.; Султанова, К. (FAN va JAMIYAT, 2016)
The article is devoted to one of the actual issues for teachers to development of critical thinking and creative abilities of students with the help of innovative methods and techniques. The authors of the article speak about the necessity of organization «School of skill». The main aim of this school is the imporovement of skill and knowledge of experienced teachers and young specialists by using the pedagogical and informational technologies in educational-upbringing process, exchange of opinions and teaching the innovative experience.